PERBEDAAN PENGETAHUAN MAHASISWA TENTANG KESEHATAN TEMPAT-TEMPAT UMUM DAN PARIWISATA DENGAN MENGGUNAKAN STRATEGI PROJECT BASED LEARNING DAN STRATEGI KONVENSIONAL - ERIAN FATRIA (HUMAN CARE JOURNAL, 2023)
The role of the lecturer in learning activities is as a facilitator who is able to prepare materials, use media, strategies that are effective and fun for students. However, in reality, in the context of implementing an independent curriculum, many lecturers apply non-innovative recovery strategies, which tend to cause student learning outcomes to not be achieved. This study aims to determine differences in student knowledge about the health of public places and tourism by applying project based learning strategies and conventional strategies. This research was conducted at Prima Nusantara University, Bukittinggi in March 2023 - August 2023. The research method was an experimental method, involving 2 classes, namely the experimental class using project based learning strategies and the control class using conventional strategies. The sample chosen was 60 students selected through multistage random sampling. The data analysis technique used in this research is the t-test used in comparative studies. The research results show that there are differences in student knowledge in public places and tourism health courses by applying project based learning strategies and conventional strategies in the context of implementing the independent curriculum. Therefore it is concluded that the project based learning strategy is effective to be implemented in order to increase student knowledge in the context of implementing the independent curriculum in tertiary institutions.